2004
DOI: 10.1523/jneurosci.0462-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Synaptic IntegrationIn VivoIs Disrupted by Amyloid-β Plaques

Abstract: The accumulation of amyloid-␤ protein into plaques is a characteristic feature of Alzheimer's disease. However, the contribution of amyloid-␤ plaques to neuronal dysfunction is unknown. We compared intracellular recordings from neocortical pyramidal neurons in vivo in APP-Sw (Tg2576 transgenic mice overexpressing amyloid precursor protein with the Swedish mutation) transgenic mice to age-matched nontransgenic cohortsatageseitherbeforeorafterdepositionofcorticalplaques.Weshowthattheevokedsynapticresponseofneuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
153
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(169 citation statements)
references
References 50 publications
13
153
1
2
Order By: Relevance
“…However, our results, as well as the results of other studies (Urbanc et al, 2002;Spires et al, 2005) suggest that β-amyloid deposition may be associated with sublethal neuronal damage (i.e., synapse loss). Also, intracellular recordings from pyramidal neurons in Tg2576 mice show that β-amyloid plaques are associated with defects in cortical synaptic integration (Stern et al, 2004) and morphological studies in Tg2576 mice show that β-amyloid plaques are related to decreases in dendritic spine density (Lanz et al, 2003;Moolman et al, 2004;Tsai et al, 2004;Spires et al, 2005). Finally, Urbanc et al (2002) found that thioflavin-S positive plaques (fibrillar plaques) are selectively neurotoxic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results, as well as the results of other studies (Urbanc et al, 2002;Spires et al, 2005) suggest that β-amyloid deposition may be associated with sublethal neuronal damage (i.e., synapse loss). Also, intracellular recordings from pyramidal neurons in Tg2576 mice show that β-amyloid plaques are associated with defects in cortical synaptic integration (Stern et al, 2004) and morphological studies in Tg2576 mice show that β-amyloid plaques are related to decreases in dendritic spine density (Lanz et al, 2003;Moolman et al, 2004;Tsai et al, 2004;Spires et al, 2005). Finally, Urbanc et al (2002) found that thioflavin-S positive plaques (fibrillar plaques) are selectively neurotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…Synapse loss induced by Aβ remains a likely basis for the behavioral deficits observed in Tg2576 mice, since Aβ has been shown to disrupt neuronal function (Stern et al, 2004) and decrease dendritic spine density (Knowles et al, 1998;Lanz et al, 2003;Moolman et al, 2004;Tsai et al, 2004;Spires et al, 2005). However, studies using synaptophysin immunohistochemical staining under light microscopy have not produced consistent findings of synapse loss in Tg2576 mice.…”
Section: Introductionmentioning
confidence: 99%
“…We focused our structural assessments on the hippocampal formation because these structures play a major role in learning and memory (Knowles, 1992;Bannerman et al, 2001) and is also a site for Ab deposition in AD patients (Probst et al, 1983;West et al, 2004) and in several transgenic mouse models of AD (Su and Ni, 1998;Reilly et al, 2003). Synapse loss induced by Ab remains a likely basis for the behavioral deficits observed in Tg2576 mice (Stern et al, 2004). Previously, we demonstrated spatial and temporal relationships between synapse loss and Ab deposition in the dentate gyrus of Tg2576 mice at 6-9 months of age .…”
Section: Introductionmentioning
confidence: 99%
“…38 Therefore, we investigated effective connectivity changes in patients with aMCI based on the activation patterns. We applied GCM to investigate how parietal activation increases were related to the recruitment of other areas, and thus to possible compensation or disconnection.…”
Section: Example Of Task Stimuli and Activation Patternsmentioning
confidence: 99%